Prevention and treatment of human papillomavirus in men benefits both men and women - Zou, Kangni; Huang, Yue; Li, Zhengyu (Frontiers in Cellular and Infection Microbiology, 2022)
Men should not be overlooked in research on human papillomavirus (HPV) and its associated genital diseases. This is because men infected with HPV are not only at higher risk of genital cancers, but also increase their partners’ risk of HPV infection and reinfection through sexual contact. Herein, we summarized the state of knowledge regarding the prevention and treatment of HPV infection in men as well as the possible effects of the prevention and treatment of HPV in men on their female partners. Condom use, smoking cessation, male circumcision, and HPV vaccination for men each play an important role in preventing HPV infection within heterosexual couples. Additionally, men could choose to test for certain types of HPV, such as the oncogenic HPV16 or HPV18 strains, as part of a routine screening program when their partner is positive for HPV. Although there is no recognized treatment for HPV infection as of yet, immunotherapy drugs, such as toll-like receptor agonists, therapeutic HPV vaccines, and immune checkpoint inhibitors, have shown promising results in clinical trials and in actual clinical practice. HPV infection in men also increases the risk of cervical cancer in their female partners. Because of the high partner concordance for HPV demonstrated in prior research, the prevention and treatment of HPV in men should be explored more comprehensively in future research.